Improvement Potential Hydroelectric Power (Hydropower) Supports Global Sustainability - Wenno, Leony Ariesta; Ngantung, Axl J.V; Batudaka, Arauna P; Wokas, Kelvinsky N; Lumempow, Dirly (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Hydroelectric Power Plant (PLTA) is a renewable energy source that plays an important role in fulfilling electricity needs in a sustainable way. This study aims to comprehensively analyze the development potential of hydroelectric power plants in supporting global energy sustainability by examining technical efficiency, economic viability, environmental impacts, and social implications through systematic evaluation of international best practices and mitigation strategies. The research methodology employs a systematic literature review approach, analyzing data from peer-reviewed academic journals, international energy organization reports (IEA, IRENA, WEC), and policy documents from multiple countries including Norway, Canada, Brazil, and China, with data categorized into technical, economic, environmental, and social aspects for comprehensive evaluation. Research results show that the hydroelectric power plant has superiority in provide electricity with supply stable and efficient high. Key findings demonstrate that modern hydroelectric technologies achieve remarkable performance: Kaplan and bulb turbines increase energy conversion efficiency significantly, Pumped-Storage Hydroelectricity (PSH) technology enhances system flexibility and grid stability, operational costs remain 60% lower than fossil fuel plants over long-term periods, and hydropower contributes to avoiding over 3 billion tonnes of CO? emissions annually while supporting flood control and water resource management. The research implications indicate that successful hydropower development requires integrated approaches combining technological innovation, supportive policies, environmental protection measures, and active community engagement to achieve optimal sustainability outcomes while maintaining economic viability and social acceptance.